Images of Brazil in the 20th-century classical music : reflections about Brazilian cultural identities (Per Musi, 2015)
This article discusses the process of image construction in the elaboration of the cultural identity expressed in the Brazilian classical music during the twentieth century. Conceptual issues related to the narrative, image creation, and cultural identity essential tothe understanding of Brazilian culture as a system of cultural representationsare discussed. Central references on the emergence ofsignificant relationships between certain musical materials and elements of the Brazilian culture (SALLES, 2005; KATER, 2001; CONTIER, 1978)are outlined. Departingfrom the definitionsof subject, identity, sense of belonging, culture and national identity, it explainsthe process of narrative and image construction around a national cultural identity. Finally,it aims atunderstandingthe relativity of the collective self-images (REZENDE, 2009; ORTIZ, 1994) that have been made present in the Brazilian classical music in that period.